KOMPUTERISASI SISTEM STOK KERTAS BERBASIS MULTIUSER (STUDY KASUS : CV ARAYA MEDIA GRAFIKA SURAKARTA) - Lisa Ayu Wijayanti, Sri Siswanti, Muhammad Hasbi (Jurnal Ilmiah SINUS, 2015)
CV Araya is at two different locations, the first location is used as a reception order, store, settings, while the second location is used as a mold production. During this expenditure and income paper is still done manually, so when removing the paper production process, the main office which is used as an acceptance of the order does not determine the amount of paper issued to the production process, as well as when the paper entry (purchase). The research objective is to create a computerized system of stock-based multiuser. The research method of data collection, the method of observation, interview method (interview), and literature. Results of the study are Computerized System Stock multiuser CV Paper-Based Graphic Media Surakarta Araya is to change the old ways are still the manual so that it can facilitate the work and reduce errors in transaction expenses and paper data entry and othersKeywords : computerized system, the paper stock, multiuser